Piezoresistive Pressure Sensor Based on Synergistical Innerconnect Polyvinyl Alcohol Nanowires/Wrinkled Graphene Film. Issue 15 (12th March 2018) - Liu, Weijie; Liu, Nishuang; Yue, Yang; Rao, Jiangyu; Cheng, Feng; Su, Jun; Liu, Zhitian; Gao, Yihua
Abstract: Piezoresistive sensor is a promising pressure sensor due to its attractive advantages including uncomplicated signal collection, simple manufacture, economical and practical characteristics. Here, a flexible and highly sensitive pressure sensor based on wrinkled graphene film (WGF)/innerconnected polyvinyl alcohol (PVA) nanowires/interdigital electrodes is fabricated. Due to the synergistic effect between WGF and innerconnected PVA nanowires, the as‐prepared pressure sensor realizes a high sensitivity of 28.34 kPa −1 . In addition, the device is able to discern lightweight rice about 22.4 mg (≈2.24 Pa) and shows excellent durability and reliability after 6000 repeated loading and unloading cycles. What is more, the device can detect subtle pulse beat and monitor various human movement behaviors in real‐time. Abstract : The polyvinyl alcohol (PVA) nanowires serve as a dielectric layer between graphene film and interdigital electrode tuning the contact resistance. The wrinkled graphene films with hierarchical microstructures inside are used as active sensing material. The synergistic effect between wrinkled graphene films and innerconnected PVA nanowires makes the piezoresistive sensor realize a high sensitivity.